ÇİN ROMANININ ÇİN HAYATINDAKİ YERİ - Wolfram EBERHARD (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 1945)
This descriptive and correlational study examined the relationship between completion of an Informatics Techniques in Nursing course and nursing students' readiness to use medical artificial intelligence, as well as the mediating role of informatics competence in this relationship. The study was conducted with 321 nursing students at a university in eastern Turkey. Data were collected online using a Personal Information Form, the Nursing Informatics Competency Self-Assessment Scale, and the Medical Artificial Intelligence Readiness Scale. Completion of the course was not directly associated with readiness to use medical artificial intelligence (standardized coefficient=0.412, P>.05). However, informatics competence was found to fully mediate this relationship (indirect effect: standardized coefficient=3.988, 95% CI [2.900-5.133]). Course completion was associated with higher informatics competence (standardized coefficient=0.400, P<.001), and higher informatics competence was associated with greater self-reported readiness to use medical artificial intelligence (standardized coefficient=0.994, P<.001). Students' informatics competence and readiness levels were moderate. Because the measures were self-reported, the findings reflect perceived competence and readiness rather than objective performance.